Musculoskeletal pain in the lumbosacral region - A. I. Isaykin (Неврология, нейропсихиатрия, психосоматика, 2011)
Musculoskeletal pain associated with nonspecific changes in the vertebral structures and paravertebral muscles is the most common type of back pain. There is an association between back pain and education level, low physical activity, smoking intensity, and the frequency of bending and weight lifting during work; hereditary predisposition is also important. On examining a patient, it is important to rule out pain caused by a serious problem: severe somatic diseases, vertebral damages of specific etiology (injuries, neoplasms, infectious and inflammatory processes), compression damages, and psychogenic diseases. Adjacent joint diseases frequently imitate verterogenic pain. In back pain, there are most commonly three major clinical syndromes: vertebral, myogenic, and radicular. Neurological and orthopedic examinations are one of the most informative diagnostic techniques for musculoskeletal pain. Most patients with musculoskeletal pain do not need neuroimaging. Psychological factors are of great importance in the chronization of pain. Among non-drug treatments, early patient activation, walking, and swimming play a vital part; a fixing belt may be used in the acute phase. Adequate manual therapy is highly effective. Medical therapy includes nonsteroidal anti-inflammatory drugs in combination with myorelaxants, as well as therapeutic blocks. Psychotherapeutic procedures, therapeutic exercises, and antidepressants are used to treat chronic pain.